Dual-positive gastric cancer: an extremely malignant subtype of gastric cancer with high serum alpha-fetoprotein and carcinoembryonic antigen concentrations - Weixun Xie; Chengyu Hu; Hongming Liu; Zelai Wu; Bixian Luo; Xiaoying Wu; Xiaoying Wu; Chuanlei Tuo; Ziyin Deng; Han Liang; Yong Liu; Weihua Gong; et al. (Frontiers in Oncology)
BackgroundAlpha-fetoprotein-producing gastric cancer (AFPGC) is a highly malignant subtype of gastric cancer, but solely alpha-fetoprotein may fail to accurately predict the prognosis. Although the utilization of multi tumor markers could improve stratified patient management, such research in AFPGC is still blank. This study seeks to evaluate whether combining multiple tumor markers can enhance risk stratification and identify AFPGC subtypes with poor prognosis.MethodsWe first screened for patients with elevated serum CEA levels within the AFPGC cohort and evaluated their prognosis. Tumor characteristics and overall health conditions were analyzed to identify factors contributing to CEA elevation. Finally, the treatment responses of this group to different treatment modalities were also reviewed.ResultsApproximately 45% of gastric cancer patients with elevated serum AFP also show increased CEA levels, classifying them as the dual-positive gastric cancer (DPGC) subgroup. These patients exhibit significantly shorter overall survival, heightened metastasis risk, and are more susceptible to systemic inflammation, immune response dysregulation, malnutrition, and cancer-related thrombosis. The elevation in serum CEA levels may indicate gastric cancer liver metastasis and increased neutrophils. While surgery is optimal for AFPGC, DPGC patients benefit significantly from immunotherapy combined with chemotherapy.ConclusionsIn AFPGC, combining serum AFP and CEA offers a more accurate prognosis. The poor prognosis in DPGC may be associated with aggressive local properties and systemic complications. Liver metastases and increased neutrophils are associated with increased serum CEA in AFPGC. Immunochemotherapy is a viable option for DPGC patients who cannot undergo surgery.